Wanita Karier Perspektif Islam (Upaya Membangun Keluarga Sakinah): Career Women in Islamic Perspective (Efforts to Build a Harmonious Family) - Ahmad Mutohar (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
The modernity of science and technology development and growth will surely affect women's movements and activities, which from a legal perspective can introduce new variations in considering topics related to women's issues. Emancipation demands access to certain life sectors previously viewed as